Packing and Problematic Feeding Behaviors in CHARGE Syndrome: A Qualitative Analysis. (March 2016) - Hudson, Alexandra; Macdonald, Meghan; Blake, Kim
Abstract: Objective: To understand packing and problematic feeding behaviors during mealtime in individuals with CHARGE syndrome. Packing, or holding food in one's cheeks without swallowing, is an adverse feeding behavior that has been described in children with autism and Down syndrome, and in those transitioning from tube to oral feeding. It has never been described in detail in CHARGE syndrome, a genetic disorder with a high prevalence of feeding difficulties, tube feeding, and otorhinolaryngological issues. Methods: A mixed methods approach used descriptive and qualitative content analysis of interviews with parents of children, adolescents, and adults with CHARGE syndrome. Individuals had previously or were currently experiencing packing or overstuffing one's mouth with food during eating. Results: Twenty parents completed a phone interview, describing their child/adult's (2–32 years) adverse feeding behaviors. Individuals had a higher proportion of cleft palates (40%) in comparison to the general CHARGE population (15–20%). Parents reported food packing most commonly with bread and pasta (33%), and reported that food was held in cheeks for hours after a meal had ended (35%). Packing was reported to prolong mealtimes for over an hour (30%). Parents were worried about choking during eating (30%). Food packing was also reported in individuals who had never needed G/J tube feeding or feeding therapy, in addition to those who had needed both. Conclusion: This study provides an in-depth description of parents' experiences with packing and adverse feeding behaviors in individuals with CHARGE syndrome. These feeding behaviors are an important addition to the knowledge of the highly prevalent feeding difficulties in this genetic disorder. Individualized evaluation of feeding behavior should be a part of the standard otolaryngologic and feeding team practice for these patients.